Development Content Learning System (CLS) Material Corrosion Based on Project Base Learning (PjBL) with Shortened Flipped Classrooms in SMA MA - Fauzia Hanum Ikhwan; Leli Astuti; Reza Apriandi; Ismail Husni (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2021)
This study goals is to produce an e-learning to help students understand chemistry lesson eventough they can’t study in class or study in a normal condition. This research is focused development of content learning system e-learning on corossion topic based on project-based learning model using flipped classroom. This study is a research and development (R&D) method to produce a particular product, and test the effectiveness of the product. The data collection techniques used is questionnaire of product evaluation. The e-learning product validation conducted by postgraduates students of educational chemistry from Universitas Negeri Padang. The validation analysis was carried out using V aiken index. The validation of 3 aspects of content validity shows is Guide and information, this components show the average result of V about 0.833, it means this component is valid. The average result of V for material content is 0.838 and for evaluation is 0.84.For the construct validity for guide and information, which the V average result is 0.796. For the program performance the v result is 0.83 and in the design principles shows 0.777 of v result. This result conclude that the e-learning product is valid, and can be use for learning process in Senior High School.